2003 Symposium on VLSI Technology. Digest of Technical Papers (IEEE Cat. No.03CH37407)
DOI: 10.1109/vlsit.2003.1221068
|View full text |Cite
|
Sign up to set email alerts
|

Design and proof of high quality HfAlO/sub x/ film formation for MOSCAPs and nMOSFETs through Layer-by-Layer Deposition and Annealing process

Abstract: We propose a new method for high-k film growth and demonstrate its usefulness in terms of improvements of electrical characteristics of MOSCAPs and nMOSFETs. mer-by-mer 12eposition & &tealing (LL-D&A) is a key concept to reduce impurities incorporated in the film through decomposition of precursors. For HfA& (Hf75at.%), it is shown that there are big differences in physical and electrical properties between LL-D&A and conventional ALD+PDA. The maximum film thickness for annealing to effectively remove impuriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…HfO 2 , HfAlO x , and HfSiO x are the most promising candidates for high-k dielectric gate insulators due to their high thermal stability in contact with silicon and sufficient conduction-band offset. [3][4][5][6][7] HTB was used for the Hf source. [1,2] Alkoxide precursors are widely used in CVD, [8][9][10] and even in molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…HfO 2 , HfAlO x , and HfSiO x are the most promising candidates for high-k dielectric gate insulators due to their high thermal stability in contact with silicon and sufficient conduction-band offset. [3][4][5][6][7] HTB was used for the Hf source. [1,2] Alkoxide precursors are widely used in CVD, [8][9][10] and even in molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…Yamaoka et al [5] reported that Hf atoms slowly diffuse into thermally grown SiO 2 during the post deposition annealing (PDA). By utilizing this nature, we have achieved the gradual incorporation of Hf atoms into underlying SiO 2 by repeating the sequence of HfO 2 deposition and annealing through the layer-by-layer deposition and annealing (LL-D & A) process [6,7]. One cycle HfO 2 (0.1 nm thick) was deposited on 1.0 nm-thick SiO 2 layer by atomic layer deposition (ALD), followed by RTA at 750°C in nitrogen ambient to diffuse Hf atoms into an underlying SiO 2 layer.…”
Section: Methodsmentioning
confidence: 99%
“…n + poly-Si gate p-MISFETs were fabricated with 1.2-2.6-nm-thick SiO 2 films, thermally grown at 950°C, followed by deposition of 2.1-5.7-nm-thick HfAlO X (Hf: 60 at.%, Al: 40 at.%) layers using the ''layer-by-layer deposition and annealing (LL-D&A)'' technique [18]. The post deposition annealing was carried out at 650°C in O 2 .…”
Section: Device Fabricationmentioning
confidence: 99%
“…The carbon concentration in the high-k film, formed using the LL-D&A method, is lower than 1/2 that using a conventional atomic layer deposition (ALD) method. Furthermore, the film density in the high-k film deposited by the LL-D&A is about 1.1 times higher than that in the ALD film [18]. The interfacial thermal SiO 2 layer was intentionally inserted in order to separate the effects of the high-k layer from those of the IL in the leakage current.…”
Section: Device Fabricationmentioning
confidence: 99%